KESULITAN BELAJAR IPS PADA SISWA SEKOLAH DASAR : STUDI PADA SD NEGERI 1 SODONG - Intansari, Ilfi; Wulandari, Sisca; Serena Pasaribu; Annisa Risqi; Indriani, Lina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Difficulties in learning social studies are not only influenced by internal student factors, but also by external factors, such as the use of less varied learning methods, limited learning media, and a teacher-centered learning approach. Although various studies have discussed difficulties in learning social studies in general, studies that specifically identify the types of learning difficulties and their causal factors in certain elementary school contexts are still limited. This study uses a qualitative approach, namely a research approach that focuses on collecting data in the form of words, statements, behaviors, images, and relevant documents. A qualitative approach was chosen because this study seeks to understand the phenomenon of difficulties in learning social studies in depth through naturalistic descriptions and comprehensive analysis. The research subjects were 28 fourth-grade students of SD Negeri 1 Sodong who participated in the entire series of social studies learning activities. Previous studies related to difficulties in learning Social Studies (IPS) in elementary school students generally highlight certain factors separately, such as learning methods or student learning motivation, without examining the relationship between internal and external factors in a particular school context. Keywords: Difficulties in learning IPS, Qualitative approach, Elementary school students.